Traffic Signals Pre-Alerting System for Ambulance - R., Kamaladevi; M., Mohamed Hashir; Y., Godbin James (Journal of ISMAC, 2025)
It is heartbreaking to learn about the infrastructure of insufficient roads as a result of neglect for traffic rules. In these incidents, an ambulance is sent to a nearby hospital in the hope of saving the victim's life, but on the route, it faces a crowd at traffic signals. This is a problem that affects a large part of the nation. No matter how loud the siren, there will always be a crowd at traffic signals, which puts the patient at risk inside the ambulance. The traffic police's inability to effectively clear the path for the ambulance using its siren presents a serious obstacle in this dangerous scenario, as it limits their ability to intervene and change traffic signals when an ambulance approaches. The failure to determine the direction of the ambulance presents an opportunity to suggest a fix by supporting the amendment of the generic system of traffic light concepts through the use of a Peer-to-Peer Network Model. A wireless IoT concept called Peer Network is used to connect devices without the need for an internet connection. An internet-less paradigm has been proposed to execute a wireless perception of traffic signals. Using the Peer-to-Peer Protocol, all traffic signals and ambulances are connected without internet access to provide alert messages, such as transforming traffic lights into an emergency mode based on the direction from which the ambulance is approaching. Peer-to-Peer eliminates obstacles between communication devices, and the reliability of this system is greater than that of the Internet. The prototype of this model was successfully implemented using a traffic light and four NodeMCUs, with a master NodeMCU that controls all four NodeMCUs to change the traffic lights.
Keywords: Traffic signal; Ambulance; Peer network; Master-Slave